William Motherwell's Cultural Politics. - Brown, Mary Ellen (The University Press of Kentucky, 2015)
William Motherwell (1797-1835), journalist, poet, man-of-letters, wit, civil servant, and outspoken conservative, published his anthology of ballads, Minstrelsy: Ancient and Modern, in 1827. His views on authenticity, editorial practice, the nature of oral transmission, and the importance of sung performance--acquired through field collecting--anticipate much later scholarly discourse. Published after the death of Burns and the publication of Scott's Minstrelsy of the Scottish Border, ballads such as those Motherwell collected were one focus of a loose-knit movement that might be designated, c.